Towards an Effective Climate Change Regime in South Africa: Policy and Legal Developments - Du Toit, Louise (Institute of Marine and Environmental Law, 2014)
Global climate change has been recognised as 'unequivocal'. Some of the changes observed in the environment include the melting of polar icecaps, rising sea levels, as well as more extreme weather conditions including droughts, tropical cyclone activity and heavy precipitation. These impacts have been caused by a drastic increase in global levels of greenhouse gas emissions 'since 1750 as a result of human activities' and a consequent increase in global temperatures of more than half a degree Celsius since before the Industrial Revolution